Human molecular genetics - Strachan, T; Read, Andrew P (Bios Scientific Publishers, 1996)
Human Molecular Genetics 2 Tom Strachan & Andrew P. Read \"truly a Rolls Royce amongst textbooks\" — Molecular Medicine Today \"the best text to introduce students and scientists to the molecular aspects of human genetics\" — Trends in Genetics \"a beautifully crafted book\" — Journal of Medical Genetics \"addresses the gap between introductory textbooks and the primary literature. There’s no other textbook quite like it.\" — Nature Now extensively rewritten and updated, HMG2 guides students and researchers through the very latest developments in the most rapidly changing area of life science. The highly regarded structure of the bestselling first edition is retained, but a wealth of new data and features have been added to aid understanding of the principles of human molecular genetics:new material on cell types and the cell cycle, signal transduction, DNA mutation repair, and comparative genomics and evolutionnew material on recent advances in the study of gene expression and function, including the use of DNA microarraysthe latest Genome Project data including an assessment of the impact of complete genome sequences and new approaches in functional genomicsexpanded coverage of common disease susceptibilitynew section on how best to obtain the latest data from web-based resourcesa range of new figures, with many more in full colorthe early use of hierarchical figures and flow charts to introduce principles described fully in later chaptersnew two-column layout to improve clarity furtherreferences systematically updatedHMG2 is the book of choice for readers requiring an authoritative and integrated approach to human genetics.
Keywords: Molecular Biology; molekulární biologie; genetika, lékařská genetika; Genetic Therapy; genetické nemoci vrozené; genetická terapie; genom lidský; embryologie a teratologie; patologie; Genome, Human; nádory; Genetic Diseases, Inborn; biologie; Neoplasms